Plasma cell leukemia: from biology to treatment - Jelinek, Tomas; Kryukov, Fedor; Rihova, Lucie; Hajek, Roman (European journal of haematology, 2015)
Plasma cell leukemia (PCL) is a very aggressive and rare form of malignant monoclonal gammopathy characterized by the presence of plasmocytes in peripheral blood. It is classified as primary PCL occuring 'de novo', or as secondary PCL in patients with relapsed/refractory multiple myeloma. Primary PCL is a distinct clinicopathological entity from myeloma with different cytogenetic abnormalities and molecular findings, which are usually found only in advanced multiple myeloma. The clinical course is aggressive with short remissions and reduced overall survival. The diagnostic criteria are based on the percentage (>20%) and absolute number (2 × 10(9) /L) of plasma cells in peripheral blood. After establishing diagnosis, induction therapy should begin promptly which is aimed to rapid disease control and to minimize the risk of early death. Intensive chemotherapy regimens and bortezomib-based regimens, followed by high-dose therapy with autologous stem cell transplantation, are recommended. Allogeneic transplantation can be considered in younger patients. This article reviews recent knowledge of this hematological malignancy that is associated with a very poor prognosis.
Keywords: Antigens, CD; CD antigeny; exprese genu; Humans; Transplantation, Autologous; plazmocelulární leukemie; indukční chemoterapie; Gene Expression; analýza přežití; Disease Progression; Multiple Myeloma; protokoly protinádorové kombinované chemoterapie; autologní transplantace; Induction Chemotherapy; lidé; plazmatické buňky; Plasma Cells; transplantace kmenových buněk; Survival Analysis; multiple myeloma; Transplantation, Homologous; bortezomib; mnohočetný myelom; chromozomální aberace; Chromosome Aberrations; Bortezomib; prognóza; Antineoplastic Combined Chemotherapy Protocols; plasma cell leukemia; Stem Cell Transplantation; progrese nemoci; Prognosis; bone marrow transplantation; homologní transplantace; Leukemia, Plasma Cell